John Song: Modern Chinese Christianity and the Making of a New Man: (Book Review) - Ma, Tianji (Asia journal of theology, 2024)
Song Shangjie (Chinese: 宋尚節; 1901-1944), also known as John Song or John Sung, was a prominent Chinese evangelist who played a key role in the revival movement in China and Southeast Asia during the 1920s and 1930s. Numerically speaking, Song, often considered an exemplary figure of an indigenous Christian tradition independent of the West and a source of the present Christian revival in China, can rightfully be called the greatest Chinese evangelist of the 20th century. Despite controversies surrounding his biography, mission methodology, and character, Song's influence in China and Southeast Asia remains palpable to this day. Daryl Ireland, Research Associate Professor of Mission at Boston University School of Theology and the associate director of the university’s Center for Global Christianity and Mission, stands as one of the foremost authorities on the life and work of John Song. His latest work, "John Song: Modern Chinese Christianity and the Making of a New Man," is an impressive culmination of years of research efforts previously captured in individual small publications and his 2015 dissertation on John Sung.